Penerapan Manajemen Asma pada Bersihan Jalan Napas pada Pasien Asma Bronchiale di IGD RS. TK. II Makassar - Nurlaela Sari Askar; Sudarman Sudarman; Wan Sulastri Emin; Muhajirin Maliga (Wal'afiat Hospital Journal, 2025)
Bronchial asthma is a chronic inflammatory airway disease that may present with acute exacerbations characterized by bronchospasm, mucus hypersecretion, and increased work of breathing. In emergency settings, nursing care should focus on airway patency and oxygenation. To describe tripod positioning and nebulizer therapy in an acute bronchial asthma patient with ineffective airway clearance in the Emergency Department (ED). A descriptive single-case report in May 2025 at the ED of RS Tk. II Pelamonia Makassar. The intervention included tripod positioning (10 minutes) and nebulizer therapy (15 minutes), with pre- and post-assessment of respiratory rate, oxygen saturation, breath sounds, cough effectiveness, and dyspnea severity, aligned with SDKI–SLKI–SIKI reasoning. Clinical improvement was observed in this case, including reduced respiratory rate (28 to 22 breaths/min), increased oxygen saturation (92% to 97%), resolution of wheezing, more effective cough, and reduced dyspnea severity. Tripod positioning and nebulizer therapy were followed by clinical improvement in this case, while causal inference is limited due to the single-case design and potential concomitant treatments.